KETERKAITAN ANTAR SEKTOR PERTANIAN DAN INDUSTRI PENGOLAHAN DI INDONESIA (Klasifikasi 14 Propinsi Berdasarkan Tabel IO Propinsi Tahun 2000) - Dyah Hapsari Amalina; Alla Asmara (Departemen Agribisnis, FEM-IPB, 2009)
Only several studies have been conducted to determine how cross-sector linkages occur. The objectives of this study are : (1) to analyze the linkages between the manufacturing sector with the agricultural sector in the regional economy, and (2) to analyze the linkages between the manufacturing with trade, hotels and restaurants sector in the regional economy. Input-output analysis (IO) were used to find out the linkages between economic sectors. The study result shows that Lampung, South Sulawesi, South Kalimantan and North Sumatra have a strong total backward linkages and forward linkages between the manufacturing with agricultural sectors. While North Maluku, NTT, West Kalimantan, West Java, East Java and Banten are the otherwise. The results of linkage analysis between the manufacturing with trade, hotels, restaurants sector shows that there is no province in the study who had strong total backward linkages and forward linkages. Provinces which has a weak total backward linkages and forward linkages between the manufacturing with trade, hotels, restaurants sector are Lampung, Gorontalo, South Kalimantan and West Java.